(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Evaluating the applicability of the Procalcitonin testing technique and proposing solutions for developing and implementing the Procalcitonin testing technique on the Cobas E411 machine at the Laboratory Department, Chuong My General Hospital, Hanoi in 2025. Subject and method: The study employed observation, in-depth interviews with clinical doctors, healthcare staff, and data recording from reports, logbooks, and other records. Information was compiled, evaluated, and analyzed to propose solutions for implementing PCT testing. Records were kept at the Clinic and Laboratory Department from January 2023 to June 2024. Interviews were conducted with representatives, 10 clinical doctors, 10 department heads and deputy department heads, 10 laboratory staff, the head of the laboratory, and the director of the Hospital. Result: The hospital basically meets the physical infrastructure requirements, equipment, biological products, and personnel; however, there is a shortage of trained personnel for PCT testing, PCT testing is not yet included in the list of licensed and covered testing techniques under health insurance. Despite the high demand for PCT testing at the hospital, all interviewees, including department leaders, clinical doctors, laboratory staff, expressed a strong desire for the implementation of PCT testing at the facility. Conclusion: Implementing PCT testing is the demand of hospital staff, and the hospital has capacity to implement this.